Factores estresantes y fobia social en una adolescente - Villamar Contreras, Mirian Sobeida (2019)
Old age is certainly a stage in which we are exposed to losses more frequently and these are not only affective, but they can also be associated with a series of stressful psychosocial factors such as: the appearance of chronic diseases, deterioration physical, loss of sensory abilities, etc. The instruments used in the investigation fully fulfilled their purposes, contributing to the diagnosis of the disorder that was affecting the elderly. The stressful factor detected has been the loss and decrease of physical abilities in addition to the loss of their partner and the separation of their family environment causing emotional deterioration and functional disability, so it was derived that they receive psychological attention to overcome this condition. To overcome geriatric depression as a result of stressful psychosocial factors, the treatment of the cognitive approach was very useful for the elderly patient to overcome this disorder